AQUATIC BEETLES AS BIOINDICATORS OF ENVIRONMENTAL CONDITIONS IN THE WATER BODIES OF SOUTH KAZAKHSTAN - Slivinsky, G. G.; Temreshev, I. I.; Isenova, G. D.; Kozhabaeva, G. E. (Acta Biologica Sibirica, 2016)
Samples of several species of water beetles (Enoshrus bicolor (Fabricius, 1792)), Hydrochara affinis Sharp, 1873, Cybister lateralimarginalis De Geer, 1774), water quality and sediments from water bodies of South Kazakhstan were investigated. The excess of cadmium regulatory standard was detected very rare, and it was discovered only in a few samples of the aquatic beetles. This is to justify the satisfactory ecological state of water bodies in relation to this metal. The presence of lead was registered in almost all of the investigated samples of water and sediment, as well as in all the samples of aquatic beetles; this indicates the need for further monitoring of the metal contamination in the region. Zinc and copper are the vital or essential elements, but we detected significant excess of the current regulatory levels for these metals. Their concentrations in coleopteran was several times higher than in water, indicating a potential hazard of zinc and copper for ecosystems of such reservoirs. In general, it can be assumed that the aquatic beetles are quite promising targets as bio-indicators because they could easily accumulate toxic elements like heavy metals.